FDG PET‐CT imaging of therapeutic response in granulomatous lymphocytic interstitial lung disease (GLILD) in common variable immunodeficiency (CVID). (28th November 2016) - Jolles, S.; Carne, E.; Brouns, M.; El‐Shanawany, T.; Williams, P.; Marshall, C.; Fielding, P.
Summary: Common variable immunodeficiency (CVID) is the most common severe adult primary immunodeficiency and is characterized by a failure to produce antibodies leading to recurrent predominantly sinopulmonary infections. Improvements in the prevention and treatment of infection with immunoglobulin replacement and antibiotics have resulted in malignancy, autoimmune, inflammatory and lymphoproliferative disorders emerging as major clinical challenges in the management of patients who have CVID. In a proportion of CVID patients, inflammation manifests as granulomas that frequently involve the lungs, lymph nodes, spleen and liver and may affect almost any organ. Granulomatous lymphocytic interstitial lung disease (GLILD) is associated with a worse outcome. Its underlying pathogenic mechanisms are poorly understood and there is limited evidence to inform how best to monitor, treat or select patients to treat. We describe the use of combined 2‐[(18)F]‐fluoro‐2‐deoxy‐d‐glucose positron emission tomography and computed tomography (FDG PET‐CT) scanning for the assessment and monitoring of response to treatment in a patient with GLILD. This enabled a synergistic combination of functional and anatomical imaging in GLILD and demonstrated a widespread and high level of metabolic activity in the lungs and lymph nodes. Following treatment with rituximab and mycophenolate there was almost complete resolution of the previously identified high metabolic activity alongside significant normalization in lymph node size and lung architecture. The results support the view that GLILD represents one facet of a multi‐systemic metabolically highly active lymphoproliferative disorder and suggests potential utility of this imaging modality in this subset of patients with CVID. Abstract : The Figure shows combined 2‐[(18)F]‐fluoro‐2‐deoxy‐d‐glucose positron emission tomography and computed tomography (FDG PET‐CT) scanning for the assessment and monitoring of response to treatment in GLILD. The synergistic combination of functional and anatomical imaging in GLILD demonstrates a widespread and high level of metabolic activity in the lungs and lymph nodes. Following treatment with rituximab and mycophenolate there was almost complete resolution of the high metabolic activity alongside significant normalisation in lymph node size and lung architecture.